Combined impact of catchment size, land cover, and precipitation on streamflow and total dissolved nitrogen: A global comparative analysis. Issue 7 (30th July 2015) - Gallo, Erika L.; Meixner, Thomas; Aoubid, Hadi; Lohse, Kathleen A.; Brooks, Paul D.
Abstract Nitrogen (N) loading is a global stressor to fresh and salt water systems with cascading effects on ecosystem processes. However, it is unclear if generalized global response patterns exist between discharge and N sourcing and retention with respect to land cover and precipitation. Using data compiled from 78 catchments from across the world, we identified how discharge and total dissolved nitrogen (TDN) vary with precipitation and land cover and how TDN yields deviate from a generalized global response pattern. Area‐weighted discharge regressions indicate that catchment size and the absence of vegetation largely control hydrologic responses. TDN concentrations and yields varied significantly (P < 0.05) with some land cover types, but these were overall poor TDN predictors (r2 < 0.26). In 42 of 78 catchments, TDN concentrations varied independently (P > 0.05) of discharge, suggesting that these sites are less sensitive to shifts in discharge associated with global climate change, but are more sensitive to shifts in hydrologic partitioning in response to land cover change. Clustering based on precipitation and stepwise multiple linear regression analyses show a shift in TDN responses from physical transport controls on TDN sourcing at the most arid and water limited sites to climate and biologically mediated controls on TDN retention at the wetter sites. Combined, these results indicate that terrestrial systems may have differential response to changes in precipitation based on existing land use and that the impact of land use change on N fate and transport occurs within the context of climate conditions.